Differential Gene Expression Signatures of Small Auxin Up-Regulated RNA(SAUR) and Gretchen- Hagen 3 (GH3) Genes in Storage Root as Compared to Non-tuber Forming Fibrous Root of Sweet Potato ( Ipomoea batatas ) - Ravi, V; Chakarabarti, S K; Saravanan, R; Makeshkumar, T; Sreekumar, J (JOURNAL OF ROOT CROPS, 2016)
The phytohormone auxin is involved in the cell division, proliferation and initial thickening of storage root of sweet potato. The present paper reports the expression of auxin responsive functionally distinct candidate genes such as Small Auxin Up-Regulated RNA ( SAUR ) and Gretchen-Hagen 3 (GH3) genes regulated by auxin in the storage root of sweet potato. The differential expression of these auxin regulated genes were analyzed in the storage root of sweet potato as compared to non-storage root using the Gene Expression Hybridization kit (Part Number 5190-0404; Agilent). During the initial storage root development of sweet potato SAUR genes viz., OsSAUR9, OsSAUR28, OsSAUR29, OsSAUR57 were up-regulated whereas OsSAUR17, OsSAUR30, OsSAUR31 were down-regulated. These genes are presumably involved in auxin synthesis and transport, regulation of cell elongation and cell expansion, root growth, vascular tissue and interaction with cytokinin. These SAUR genes may interact with CalCaM- binding protein that acts to transduce second messenger signals into a wide array of cellular signal transduction responses involving auxin and brassinosteroid. OsGH3.1 a probable IAA amido synthase was moderately up-regulated and presumably involved in the regulation of auxin content, morphology and growth of storage root in sweet potato. Several OsGH3.8 , OsGH3.1 , OsGH3.3 and OsGH3.11 which are probable IAA-amido synthetase were down-regulated. The down-regulation of GH3.11 in the storage root relates to its interaction with jasmonic acid during storage root formation of sweet potato.